Catch, consumption, and employment survey - Sean, Vichet; Ou, Phichong; Sun, Vathanak; Freed, Sarah (2024)
Sampled households will meet one or more of the following criteria at the time of the first survey: 1) at least one household member conducted rice field fishing at least once in the past 12 months; 2) household members consumed fish at least once in the past 4 months; 3) at least one household member has earned income by trading fish (from fish harvest to market) in the past 4 months, or is currently employed in the fish trade; 4) at least one household member has been involved in other value chain activities in the past 4 months. The monitoring will be conducted in a manner to set baseline values for zone of influence catch and employment in the fishery value chain, with which subsequent monitoring results will be compared to assess change over the life of the project. The baseline values will include kg/year for fish production (including a trend over multiple years, if possible, or otherwise the previous year value for kg/year), household fish consumption, and threshold price of fish and other aquatic animals purchased by food insecure households. The Catch, consumption, and employment survey and procedures are based on the recommendations made and applied for the USAID RFFII project (see Hortle, 2012). Sampling of fishing households will be conducted four times each year, once each during flood recession, dry season, flood rising, and wet season. A minimum of 20 households are sampled per CFR site. The survey is designed to be longitudinal by revisiting the same households during each survey occasion. If a household has migrated or is unavailable during the survey period, another household will be surveyed in its place for that occasion only. Questions will be asked on the amount of household catch (including fish, other aquatic animals, and aquatic plants) by habitat and species, market price of the catch by species, use of the catch (consumption, sale, processing, livestock feed, other uses, and loss due to cleaning, discards, and/or spoilage), the number of hours household members have spent working in the fish value chain (including to manage, harvest, process, and market fish, for income or subsistence purposes), and the ID Poor status of the household. Responses will be recorded using Kobo toolbox, a mobile data collection platform. The recorded data will be used to calculate average household quantity of fish catch from rice field ecosystems in the CFR zone of influence, fish consumption, and fishery related incomes and employment. The proportion of surveyed households that fished, the average household fish catch per site from the four sampling occasions in a year, along with the estimated area of the CFR zone of influence, will be used to calculate annual rice field fishery productivity. Fishery incomes will be calculated from the average value of household catch. For employment, fishery labour hours will be reported as FTE. Numbers of fish powder producers and hours spent producing fish powder will be cross-checked with records from nutrition training groups and household visioning exercises. National population census statistics on household size, proportions of men, women, and youth and adults, will be used to convert the household averages to estimated population-level values for the indicators.